Penilaian Responsivitas Pelayanan Pasien di Rumah Sakit Umum Pratama Kabupaten Pangkajene dan Kepulauan Sulawesi Selatan - Andi Mu’tiah Sari (PPNI UNIMMAN, 2023)
The objectives of this study were out find responsiviness patient at the regional hospital Pratama of Pangkep island regency. This study uses a type qualitative descriptive with as many as 8 informant taken by purposively. Data collection techniques use observation, interviews, and documentation. Data analysis is carried out systematicly, namely data reduction, data presentation, verification, and conclusions The results of the study indicate that responsiviness is in service at the regional general hospital Pratama Pangkep Island regency consists of (3) three: (1) the ability to respond to the behavior and good respons. This is seen from modestly, friendliness, justice shown in serving; (2) the speed of service which is based on service time every day and the agility of the officer has not run smoothly in accordance with the stipulated conditions. This is because at the time of service there are still officier who are slow to handle; (3) the accuracy of service is based on service procedures and the accuracy of the officers is good. This can be seen from the accuracy of the officier and there no mistake in the service in other words the officier provides services according to the wishes and services carried out in accordance with established procedurs.